2000
DOI: 10.1155/s1023621x01000288
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inter‐row Gap Value on Turbine Losses

Abstract: This paper presents the results of a numerical investigation of the gap influence on the turbine efficiency. The rotor-stator interaction in a (1/2)-stage turbine is simulated by solving the quasi-three-dimensional unsteady Euler/Navier-Stokes equations using a parallelized numerical algorithm. The reduced turnaround time and cost/MFLOP of the parallel code was crucial to complete the numerous run cases presented in this paper. The inter-row gap effect is evaluated for 4 gaps, 3 radial positions and 3 angular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…1,6,7 However, some studies suggest a larger clearance to be more beneficial in terms of efficiency. 810…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,7 However, some studies suggest a larger clearance to be more beneficial in terms of efficiency. 810…”
Section: Introductionmentioning
confidence: 99%
“…1,6,7 However, some studies suggest a larger clearance to be more beneficial in terms of efficiency. [8][9][10] The influence of the end walls and stator-rotor interaction in the end-wall regions on the loss generation has been found to be important in many of the studied turbines. Restemeier et al 11 studied a 1.5stage low-aspect ratio axial turbine both numerically and experimentally and found that the performance improves with a decreasing axial clearance.…”
Section: Introductionmentioning
confidence: 99%